Ph‐tetraMe‐Bithienine, the First Member of the Class of Chiral Heterophosphepines: Synthesis, Electronic and Steric Properties, Metal Complexes and Catalytic Activity. Issue 36 (5th November 2013) - Vaghi, Luca; Benincori, Tiziana; Cirilli, Roberto; Alberico, Elisabetta; Mussini, Patrizia Romana; Pierini, Marco; Pilati, Tullio; Rizzo, Simona; Sannicolò, Francesco
Abstract: Unknown 1 H ‐2, 7‐dihydro‐1‐phenylphosphepine, containing a 2, 2′, 5, 5′‐tetramethyl‐3, 3′‐bithiophene atropisomeric scaffold (Ph‐tetraMe‐Bithienine), and its oxide have been synthesized and structurally characterized by single‐crystal X‐ray diffraction analysis. The most evident structural feature is the very small dihedral angle. The electronic properties of the phosphane were quantitatively evaluated by cyclic voltammetry and compared with three other 2, 7‐dihydro‐1‐phenylphosphepines differing in the nature of the biaromatic scaffold (biphenyl, 1, 1′‐binaphthyl and 2, 2′‐dimethoxybiphenyl). The racemate of the phosphane oxide was resolved into antipodes, which were reduced to the enantiopure phosphanes and employed as ligands in Rh and Pt complexes in homogeneous stereoselective catalytic reactions. The enantioselective ability and catalytic activity of the new mediators were found to be quite modest in the hydrogenation reactions of olefinic double bonds, whereas good performances were achieved in specific C–C bond‐forming reactions. The results are interpreted on the basis of the steric and electronic properties of the ligand. Abstract : Ph‐tetraMe‐Bithienine, an unknown phosphepine containing a 3, 3′‐bithiophene scaffold, and its oxide have been synthesized, resolved into antipodes, and structurally and electronically characterized. The enantioselective ability and catalytic activity of metal complexes of the ligand were investigated in C=C hydrogenation reactions and C–C bond‐forming reactions.